The high cost of cutting corners - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Animal diseases are powerful, fearful factors in our lives. Scorning boundaries, they jump from beast to beast, from wild to domesticated, and, rarely, from animal to man. A cause for great concern especially where markets might be lost but...